Tingkat Kematangan Teknologi Informasi Menggunakan Framework COBIT pada Layanan Teknologi Informasi (Studi Kasus: STIE MDP) - Desy Iba Ricoida (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
Currently a very large role of information technology in all areas of education is no exception, where the roles and appropriate management should be taken to ensure the availability of IT services that support business processes in the organization is on STIE MDP. This study aims to measure the level of maturity (maturity) of the process and information technology services applied to STIE MDP. This study uses a methodology developed COBIT framework for IT Governance Institute (ITGI) for control and auditing of IT with a focus on the domain "deliver and support (DS)". The results obtained maturity measurement of IT services at STIE MDP particular DS domain average - average - average 2.73 and was at 3-Define level while the level of maturity expected by the organization is at an average level of 3.9 is Managed and measurable. Recommendations increase the level of maturity with more emphasis on DS DS 5 and 11 who get the smallest maturity calculation domain than other processes.